Option for Land and Water Management to Prevent Fire in Peat Land Areas of Sumatera, Indonesia - Momon Sodik Imanudin; Elisa Wildayana; M. Edi Armanto (Center for Journal Management and Publication, 2018)
Investment development for oil palm plantation in Indonesia was increasing and it clear away into peat land area. Land clearing activities without considering peat ecological function may have impact on environmental degradation. The objective of this research was to study development potential of oil palm plantation at peat land by using land evaluation approach. The field survey method was observation scale and land suitability assessment was based on FAO standard with adjustment. Assessment results showed that land had peat thickness higher than 3 m covering 28% of total area so that it can be opened for oil palm plantation. The main constraint factors for the clearing of feasible area were soil reaction, flooding condition and nutrients status. These parameters could be potentially improved. However, final assessment of land showed that it was classified as less feasible (S2) due to relatively high investment.Â Cultivation can only be conducted with provision of drainage facility. Caution should be taken in designing open channel in order to prevent excessive water drainage. Therefore, hydrologic analysis can be based on 5 years return period only. Computer simulation of DRAINMOD was applied to determine the operational effect of control structures in elevating of water table during dry season. Simulation results showed that during the opening operation of open channel without control structures at dry season, water table was dropped up to 90 cm below soil surface. Water retention effort in tertiary channel at 70 cm level could elevated water up to 30-40 cm below soil surface. The key success for oil palm plantation development at peat land was highly depended on availability of control structure at tertiary channel. Flap water gate type from fibre material was very suitable for field application. Retention system by using soil sack or stoplog water gate could be implemented at initial stage in order to economize the cost.Â Â